PENGUKURAN KUALITAS WEBSITE KOTA ADMINISTRASI JAKARTA UTARA TERHADAP KEPUASAN PENGGUNA MENGGUNAKAN METODE WEBQUAL 4.0 - Rachma Dien; Iwan . (Jurnal informasi dan komputer, 2022)
Based on Presidential Instruction No. 3 of 2003, the government in this case the Ministry of Communication and Information has established a National Policy and Strategy on the development of e-government. So that a quality government website is demanded. Based on that, this research is to measure the quality of the website of the North Jakarta administration city government, namely https://utara.jakarta.go.id/ which is viewed from the side of end user satisfaction. The purpose of this study was to determine the quality of the North Jakarta administration city website and to provide recommendations for improving the North Jakarta administration city website in improving the quality of information services. The sample of this study included 100 respondents who were calculated based on the Slovin formula and used the purposive sampling technique. This study uses the webqual 4.0 method which consists of three independent variables, namely usability, information quality and interaction quality and 1 dependent variable, namely user satisfaction. The results obtained from the t-test show that the dimensions of ease of use and the dimensions of information quality have no effect on the dimensions of user satisfaction and only the interaction quality variables that affect user satisfaction. The results obtained from the f test show that the variables usability, information quality and interaction quality simultaneously affect the user satisfaction variable by 49% while the remaining 51% possibly influenced by factors other than the webqual 4.0 variable.